Genetic lineage tracing reveals poor angiogenic potential of cardiac endothelial cells. Issue 1 (30th January 2020) - Kocijan, Tea; Rehman, Michael; Colliva, Andrea; Groppa, Elena; Leban, Matteo; Vodret, Simone; Volf, Nina; Zucca, Gabriele; Cappelletto, Ambra; Piperno, Giulia Maria; Zentilin, Lorena; Giacca, Mauro; et al.
Abstract: Aims: Cardiac ischaemia does not elicit an efficient angiogenic response. Indeed, lack of surgical revascularization upon myocardial infarction results in cardiomyocyte death, scarring, and loss of contractile function. Clinical trials aimed at inducing therapeutic revascularization through the delivery of pro-angiogenic molecules after cardiac ischaemia have invariably failed, suggesting that endothelial cells in the heart cannot mount an efficient angiogenic response. To understand why the heart is a poorly angiogenic environment, here we compare the angiogenic response of the cardiac and skeletal muscle using a lineage tracing approach to genetically label sprouting endothelial cells. Methods and results: We observed that overexpression of the vascular endothelial growth factor in the skeletal muscle potently stimulated angiogenesis, resulting in the formation of a massive number of new capillaries and arterioles. In contrast, response to the same dose of the same factor in the heart was blunted and consisted in a modest increase in the number of new arterioles. By using Apelin-CreER mice to genetically label sprouting endothelial cells we observed that different pro-angiogenic stimuli activated Apelin expression in both muscle types to a similar extent, however, only in the skeletal muscle, these cells were able to sprout, form elongated vascular tubes activating Notch signalling, and became incorporated into arteries. In the heart, Apelin-positive cells transiently persisted and failed to give rise to new vessels. When we implanted cancer cells in different organs, the abortive angiogenic response in the heart resulted in a reduced expansion of the tumour mass. Conclusion: Our genetic lineage tracing indicates that cardiac endothelial cells activate Apelin expression in response to pro-angiogenic stimuli but, different from those of the skeletal muscle, fail to proliferate and form mature and structured vessels. The poor angiogenic potential of the heart is associated with reduced tumour angiogenesis and growth of cancer cells. Graphical Abstract: